Pregnancy weight gain by gestational age and stillbirth: a population‐based cohort study. (28th December 2017) - Johansson, K; Hutcheon, JA; Bodnar, LM; Cnattingius, S; Stephansson, O
Abstract : Objective: To study the association between total and early pregnancy (<22 completed weeks) weight gain and risk of stillbirth, stratified by early‐pregnancy body mass index (BMI). Design: Population‐based cohort study. Setting: Stockholm‐Gotland Region, Sweden. Population: Pregnant women with singleton births ( n = 160 560). Methods: Pregnancy weight gain was standardised into gestational age‐specific z‐scores. For analyses of total pregnancy weight gain, a matched design with an incidence density sampling approach was used. Findings were also contrasted with current Institute of Medicine (IOM) weight gain recommendations. Main outcome measures: Stillbirth defined as fetal death at ≥22 completed weeks of gestation. Results: For all BMI categories, there was no statistical association between total or early pregnancy weight gain and stillbirth within the range of a weight gain z‐score of −2.0 SD to +2.0 SD. Among normal‐weight women, the adjusted odds ratio of stillbirth for lower (−2.0 to −1.0 SD) and higher (+1.0 to +1.9 SD) total weight gain was 0.85 (95% CI; 0.48–1.49) and 1.03 (0.60–1.77), respectively, as compared with the reference category. Further, there were no associations between total or early pregnancy weight gain and stillbirth within the range of weight gain currently recommended by the IOM. For the majority of the BMI categories, the point estimates at the extremes of weight gain values (<−2.0SD and ≥2.0 SD) suggested protective effects of low weight gain and increased risks of high weight gain, but estimates were imprecise and not statistically significant. Conclusion: We found no associations between total or early pregnancy weight gain and stillbirth across the range of weight gain experienced by most women. Tweetable abstract: There was no association between weight gain during pregnancy and stillbirth among most women. Abstract : Tweetable abstract There was no association between weight gain during pregnancy and stillbirth among most women.